OPTIMALISASI MANAJEMEN LOGISTIK BERBASIS TEKNOLOGI INFORMASI GUNA MENDUKUNG OPERASIONAL PENGAMANAN MUDIK LEBARAN PARIPURNA COVID-19 - Soecipto Soecipto (Media Nusantara, 2022)
ABSTRACT IN ENGLISH VERSION: In contrast to the previous two years, the government allowed people to go home for Eid in 2022. The government has optimism that the 2022 Eid homecoming implementation can run safely from the COVID-19 attack. In fulfilling the logistics of the Police, especially in meeting the needs for infrastructure, there are several logistical errors, namely: 1) Errors in planning facilities and infrastructure; 2) Incorrect procurement, both in terms of quantity and type of equipment; 3) Wrong in equipment distribution; 4) Weaknesses in the misuse of infrastructure facilities; 5) Delivery, storage and use that are not in accordance with the proper standards, resulting in equipment defects; 6) Specific errors in storage within a certain time; 7) Errors in equipment maintenance; 8) Lack of supervision and control resulting in equipment being lost, damaged or not functioning properly. The research method is a qualitative research with a literature study method, research The research method is a qualitative research with literature study methods, descriptive research and field observations. The reason this method is used is because there is still a pandemic threat and very high activity from the police so that data cannot be searched in the field. In large numbers, the sample population/subjects are UNINUS postgraduate postgraduate students who are also members of the National Police. The place and time are the Nusantara Islamic University Campus, West Java Regional Police and several homecoming post points, . The result is the conclusion that there is a need for strict monitoring and monitoring of the homecoming flow and recommendations to the police leadership. Berbeda dengan dua tahun sebelumnya, pemerintah mengizinkan masyarakat melakukan mudik Lebaran pada tahun 2022 ini. Pemerintah memiliki optimisme penyelenggaraan mudik Lebaran 2022 dapat berjalan aman dari serangan COVID-19. Dalam pemenuhan logistik Polri khususnya dalam pemenuhan kebutuhan sarana prasarana terdapat beberapa kesalahan logistik yaitu : 1) Kesalahan dalam perencanaan sarana dan prasarana ; 2) Salah dalam pengadaan baik dari sisi jumlah maupun jenis peralatan; 3) Salah dalam distribusi peralatan ; 4) Kekurangan dalam kesalahan pemakaian sarana prasarana; 5) Pengiriman, penyimpanan dan penggunaan yang tidak sesuai standar yang seharusnya sehingga menimbulkan kecacatan peralatan; 6) Kesalahan khusus dalam penyimpanan dalam waktu tertentu; 7) Kesalahan dalam perawatan peralatan; 8) Kurangnya pengawasan dan kontrol yang mengakibatkan peralatan hilang, rusak atau tidak berfungsi dengan baik. Metode penelitian merupakan penelitian kualitatif dengan metode studi literatur, penelitian Metode penelitian merupakan penelitian kualitatif dengan metode studi literatur, penelitian deakriptif dan observasi di lapangan alasan  metode ini digunakan karena masih adanya ancaman pandemi serta kesibukan yang sangat tinggi dari aparat kepolisian sehingga tidak dapat dicari data dalam jumlah besar, populasi sampel /subjek adalah mahasiswa pasca sarjana S2 UNINUS yang juga merupakan anggota Polri. Tempat  dan  waktu adalah Kampus Universitas Islam Nusantara, POLDA Jawa Barat dan beberapa titik posko mudik, . Hasilnya adalah kesimpulan perlunya pemantauan dan monitor ketat arus mudik dan rekomedasi ke pimpinan Polri.